Tetanus toxin production is triggered by the transition from amino acid consumption to peptides. (October 2016) - Licona-Cassani, Cuauhtemoc; Steen, Jennifer A.; Zaragoza, Nicolas E.; Moonen, Glenn; Moutafis, George; Hodson, Mark P.; Power, John; Nielsen, Lars K.; Marcellin, Esteban
Abstract: Bacteria produce some of the most potent biomolecules known, of which many cause serious diseases such as tetanus. For prevention, billions of people and countless animals are immunised with the highly effective vaccine, industrially produced by large-scale fermentation. However, toxin production is often hampered by low yields and batch-to-batch variability. Improved productivity has been constrained by a lack of understanding of the molecular mechanisms controlling toxin production. Here we have developed a reproducible experimental framework for screening phenotypic determinants in Clostridium tetani under a process that mimics an industrial setting. We show that amino acid depletion induces production of the tetanus toxin. Using time-course transcriptomics and extracellular metabolomics to generate a 'fermentation atlas' that ascribe growth behaviour, nutrient consumption and gene expression to the fermentation phases, we found a subset of preferred amino acids. Exponential growth is characterised by the consumption of those amino acids followed by a slower exponential growth phase where peptides are consumed, and toxin is produced. The results aim at assisting in fermentation medium design towards the improvement of vaccine production yields and reproducibility. In conclusion, our work not only provides deep fermentation dynamics but represents the foundation for bioprocess design based on C. tetani physiological behaviour under industrial settings. Highlights: High resolution transcriptomics and metabolomics map in pathogenic clostridia mimicking an industrial process. Exponential growth is characterised by the consumption of amino acids in Clostridium tetani . Toxin production is triggered at the transcriptional level by a nutritional switch – from amino acids to peptide consumption.